PENGARUH KONSENTRASI DAN INTERVAL PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L.) - Antono, Yulian; yulia, Arnis en (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The Research aimed to determine the effect of liquid organic fertilizer concentration and interval application on growth and production of mung bean in order to get dosage. This research was conducted at the experimental station of Agriculture Faculty of Riau University, from january 2017 to april 2017, by using randomized block design (RBD) method, 3 replicarions, which consist of two factors. The first factor is, the concentration of liquid oraganic fertilizer dosage consisted of 4 levels (0, 15, 25 and 35 ml/l) and the second factor is, interval application of organic liquid fertilizer, consisted 3 levels (5, 10 and 15 days). The parameters observed were plants height, brunch number, flowering age, pod total, filled out pod percentation, 100 seed weight, and production per plot (4 m2). Observationts of each parameter were analyzed statistically using analysis of variance and Duncan's new multiple range test (DNMRT) with level of 5%. The results show that the concentration of liquid organic fertilizer 15 ml/l and interval 10 days is the appropriate dosage to increase the growth and production of mung bean.Keywords: Mung Bean, Liquid organic fertilizer